Successful Preoperative Treatment by Plasmapheresis of Hyperthyroidism with Hydatidiform Mole - Cem Onur KIRAÇ; Süleyman BALDANE; Ayşe Gül KEBAPÇILAR; Süleyman Hilmi İPEKÇİ; Mustafa Gazi UÇAR; Çetin ÇELİK; Levent KEBAPÇILAR (Bezmiâlem Science, 2018)

(untitled)
We recently encountered the case of an 18-year-old female complaining of abdominal pain, fatigue, nausea, vomiting, tremor of the hands, and vaginal bleeding. Her blood test revealed highly elevated human chorionic gonadotropin (hCG) levels, suppressed thyroid-stimulating hormone (TSH) levels, and increased free thyroid hormone levels. Molar pregnancy and hyperthyroidism were suspected based on highly elevated hCG levels and suppressed TSH levels with the co-existence of ultrasonographic findings of the uterus and thyroid Doppler images. Her symptoms and thyroid hormone levels responded well to plasmapheresis. Subsequently, the patient underwent dilatation and curettage for hydatidiform mole. Histopathology of the products verified the diagnosis of complete hydatidiform mole with no invasion. The patient is currently stable, and her hCG and thyroid hormone levels are within normal reference ranges.